Greek-style yogurt enriched with shield aralia leaves improves lactation hormones in rats - Pertami, Sumirah Budi; Yunitasari, Esti; Krisnana, Ilya; Budiono, Budiono; Herawati, Tutik (Journal of Food Technology Research, 2026)
Exclusive breastfeeding for six months is essential to provide adequate nutrition for infants. However, hypogalactia or insufficient breast milk production presents challenges during lactation. Herbal galactagogues have been traditionally used to maintain breast milk production. Polyscias scutellaria leaves are believed to possess galactagogue properties. This study aimed to evaluate the galactagogue properties of P. scutellaria yogurt in lactating rats. Twenty-five lactating rats were divided into five groups: unmated rats (UR), negative control lactating rats (NCR), positive control lactating rats (PCR), lactating rats treated with P. scutellaria yogurt at 2 g/kg BW (LRPSY1), and 4 g/kg BW (LRPSY2). Treatments were administered orally during a 3-week lactation period. The weekly body weight of dams and pups, prolactin, and oxytocin levels were examined. Prolactin and oxytocin were measured using enzyme-linked immunosorbent assay (ELISA). Results showed that the body weight of dams decreased while the body weight of pups increased following supplementation with P. scutellaria yogurt. Weekly prolactin and oxytocin levels increased significantly compared with the PCR group, which was treated with domperidone. At the third week of lactation, prolactin levels in the PCR group were 83.55 ng/mL, while LRPSY1 and LRPSY2 showed higher levels at 150.17 and 114.55 ng/mL, respectively. Furthermore, oxytocin levels at the third week of lactation were significantly higher in LRPSY1 (33.88 ng/mL) and LRPSY2 (35.33 ng/mL) compared with the PCR group (22.05 ng/mL). The increase in prolactin and oxytocin correlated with enhanced breast milk production. This study suggests that P. scutellaria yogurt has the potential to increase breast milk during lactation.